A Layered Model for AI Governance - Gasser, Urs; Almeida, Virgilio A. F. (IEEE internet computing, 2017)
AI-based systems are "black boxes," resulting in massive information asymmetries between the developers of such systems and consumers and policymakers. In order to bridge this information gap, this article proposes a conceptual framework for thinking about governance for AI.